Medical Drone – A Life Saver in Emergency Situations - Josephin Arockia Dhivya, A; J. Hemalatha, R; R.Thamizhvani, T; Elsa Joseph, Josline; Babu, Bincy; Chandrasekaran, R (International Journal of Engineering and Technology, 2018)
Many thousands of humans are dying day to day due to the delay of ambulances reaching the accident spot at right time.So this prototype explains clearly about the emergent situation of a drone reaching the accident scenario with various sensors.The usage of this technology gradually decreases the fatal cases.It is used to save time and helps in patientâ€™s survival.The technology works such like different types of sensors are fitted to the health drone.When a phone call is given to a prescribed given number,the operator thereby tracks the location and the navigation of the place is tracked using global positioning system.The medical quadcopter or drone arrives at the critical situation and various modes of parameters from the body are measured.This prototype gives the information of the patient to both the hospital sources and the nurses present in the normal ambulance.This flying medical drone reach the spot before the normal ambulance arrives the scene.It also measures the real time actual situation of the patient and it helps in saving a life of a patient.The information regarding the patients health parameters will be sent to concerned hospital staffs and to the respective staffs coming in the ambulance. This helps the paramedics and the doctors to know about the patientâ€™s condition before arriving the spot.This medical drone acts as a tool kit which flies to various emergency Situation. ambulance and the hospital team so that they will be ready to serve to the needs of the patients.The proposed prototype model is used as a support the persons who need immediate attention.Â